Cytomegalovirus retinitis, in a diabetic immunocompetent patient, after intravitreal ranibizumab injection. Issue 1 (January 2019) - Zafeiropoulos, Paraskevas; Tamboura, Polykseni; Dimou, Maria; Christodoulou, Eleni; Stefaniotou, Maria
We here report a case of cytomegalovirus retinitis in a diabetic patient that occurred after intravitreal ranibizumab injection. A 75-year-old woman was treated with intravitreal ranibizumab injections for diabetic macular edema. During this period, a retinitis occurred in her left eye along with increased IgG and later IgM cytomegalovirus antibody titers. Ocular and intravenous ganciclovir was administered. Cytomegalovirus retinitis subsided post treatment with residual areas of retinal atrophy. Ophthalmologists should be aware of the incidence of cytomegalovirus retinitis, in diabetic patients, after ranibizumab injection.